The HOX11 gene encodes a DNA-binding nuclear transcription factor belonging to a distinct family of homeobox genes. - T. Neil Dear; Isidro Sánchez‐García; Terence H. Rabbitts (1993)
A translocation involving human chromosome 10, band q24, in a subset of T-cell acute leukemias disrupts a region surrounding the putative oncogene HOX11, which encodes a protein with a homeodomain. The HOX11 protein binds to a specific DNA sequence, it localizes to the cell nucleus, and it transactivates transcription of a reporter gene linked to a cis-regulatory element, suggesting that HOX11 functions in vivo as a positive transcription activator. PCR analysis shows that the HOX11 homeodomain is a member of a distinct class of homeodomains, representatives of which occur in murine and Drosophila genomes. These all contain a threonine residue in place of the more common isoleucine or valine in helix 3 of the homeodomain. HOX11 therefore appears to belong to a family of DNA-binding transactivators of transcription.